2021
DOI: 10.1073/pnas.2023297118
|View full text |Cite
|
Sign up to set email alerts
|

Storage of carbon reserves in spruce trees is prioritized over growth in the face of carbon limitation

Abstract: Climate change is expected to pose a global threat to forest health by intensifying extreme events like drought and insect attacks. Carbon allocation is a fundamental process that determines the adaptive responses of long-lived late-maturing organisms like trees to such stresses. However, our mechanistic understanding of how trees coordinate and set allocation priorities among different sinks (e.g., growth and storage) under severe source limitation remains limited. Using flux measurements, isotopic tracing, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…In addition, stand rejuvenation through harvesting and the replanting of saplings, with less 'respiring' (live) biomass per unit of photosynthetic leaf area (because of a shift toward younger stands), and combined with the fertilization effects of increased atmospheric CO 2 concentration can potentially drives to more productive and efficient forests. This is mirrored in the observed capability of trees to partition more of the photosynthetically assimilated carbon into new woody biomass rather than into nonstructural 19 carbon pools (Campioli et al, 2015;Pappas et al, 2020;Collalti et al, 2020a;Huang et al, 2021). This aspect is reflected in the increasing Harvested Wood Products (HWP; Figure S7) over time with more frequent thinning, reduced tree density, replacement and presence of younger forest stands that potentially can remain in the system as standing biomass over the long-term (Figure S8).…”
Section: Limited Leeway To Increase Carbon Uptake and Woody Stocks Wi...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, stand rejuvenation through harvesting and the replanting of saplings, with less 'respiring' (live) biomass per unit of photosynthetic leaf area (because of a shift toward younger stands), and combined with the fertilization effects of increased atmospheric CO 2 concentration can potentially drives to more productive and efficient forests. This is mirrored in the observed capability of trees to partition more of the photosynthetically assimilated carbon into new woody biomass rather than into nonstructural 19 carbon pools (Campioli et al, 2015;Pappas et al, 2020;Collalti et al, 2020a;Huang et al, 2021). This aspect is reflected in the increasing Harvested Wood Products (HWP; Figure S7) over time with more frequent thinning, reduced tree density, replacement and presence of younger forest stands that potentially can remain in the system as standing biomass over the long-term (Figure S8).…”
Section: Limited Leeway To Increase Carbon Uptake and Woody Stocks Wi...mentioning
confidence: 99%
“…This outcome, combined with the fertilization effects of increased atmospheric CO 2 concentration and less 'respiring' (live) biomass per unit of photosynthetic (leaf) area (because of shift toward younger stands), potentially drives more productive and efficient forests. This is mirrored in the capability for trees to allocate (partition) more of the photosynthetically assimilated carbon into new woody biomass rather than into nonstructural carbon pools to maintain living woody tissues (Vicca et al 2012;Campioli et al, 2015;Malhi et al, 2015;Pappas et al, 2020;MartĂ­nez-Vilalta et al, 2016;Collalti et al, 2020a;Huang et al, 2021). This is directly mirrored by the increasing HWP over time with more frequent thinning, reduced tree density, replacement and presence of younger forest stands (a component of the pCWS, see for HWP dynamic Figure S7) which potentially can remain in the system (the other component of the pCWS, see for standing woody biomass dynamic preprint (which was not certified by peer review) is the author/funder.…”
Section: Limited Leeway To Increase Carbon Uptake and Woody Stocks Wi...mentioning
confidence: 99%
“…Yu et al: Contrasting drought legacy effects on GPP in a mixed vs. pure beech forest Drought impacts on terrestrial ecosystems are not limited to concurrent effects but also include legacy effects during the following seasons and years (Anderegg et al, 2015;Frank et al, 2015;Kannenberg et al, 2020;MĂŒller and Bahn, 2022). Legacy effects at tree and/or stand scale can be caused by the higher vulnerability to drought due to previous water depletion of the soil (Krishnan et al, 2006, Galvagno et al, 2013, reduced or delayed leaf development (Migliavacca et al, 2009;Rocha and Goulden, 2010;Kannenberg et al, 2019), drought-induced hydraulic damage of the xylem (Anderegg et al, 2013), adjustments in carbon allocation within the trees (Huang et al, 2021), depletion of non-structural carbohydrates (Peltier et al, 2022) due to reduced carbon availability and adjustments in carbon allocation (Hartman and Trumbore, 2016), and tree mortality (Allen et al, 2015), as well as reduced resistance to disturbances (e.g. insect outbreaks) due to depleted non-structural carbohydrates (Erbilgin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, there is also experimental evidence indicating that trees actively store starch at the expense of growth. [7][8][9] Multiple studies have indicated a role for starch in providing carbon and energy when photosynthesis or sugar transport is limited, e.g., during dormancy, bud flush, or stress. 8,[10][11][12][13][14] A genetic link between seasonal starch content variation and stress has been observed for genomic variation connected to carbon storage in Populus trichocarpa.…”
Section: Resultsmentioning
confidence: 99%